Implementasi Dakwah di Desa Pinangratus dalam Meningkatkan Kebersamaan Antarmasyarakat dengan Kegiatan-Kegiatan Sosial - Tanjung, Sri Rezeki; Panggabean, Juwita Yanti; Reyhan, Aisyah; Aulia, Rizky (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Conducting da'wah in a diverse community is not just about holding strong beliefs, but also about embodying strong moral principles and social ethics. This study discusses the implementation of da'wah in the Pinangratus village, focusing on efforts to enhance community solidarity through social activities. Pinangratus village is a heterogeneous environment, where various social and cultural backgrounds coexist. The aim of this research is to reveal how da'wah in this village can serve as a means to strengthen social relationships and increase solidarity among residents. The study uses qualitative research methods, involving observation, interviews, and document analysis to collect data. The results show that the implementation of da'wah in Pinangratus has successfully created a variety of social activities involving the entire village community. These activities include the development of social infrastructure, educational programs, health assistance, and various religious activities involving all villagers, regardless of their social or cultural background.